Pengaruh Jumlah Bibit dan Pupuk Organik terhadap Pertumbuhan dan Hasil Tanaman Padi (Oryza sativa L.) - IVAN MATHEUS NAINGGOLAN; GEDE WIJANA; I GUSTI NGURAH SANTOSA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2017)
The Effect of Number of Seeds and Organic Fertilizer on the Growth and Yield of Rice (Oryza sativa L.) This research aims to determine the effect of the number of seedling and organic fertilizers solid and liquid on the growth and yield of rice plants. The research was conducted on March 18 - July 3 2016 at the Greenhouse Garden Experiments Faculty of Agriculture, University of Udayana, Denpasar. The research method is a pattern of split plot using randomized block design consists of two factors: the main plot (organic fertilizer) and subplot (use the number of seeds). The main plot consisted of two levels are solid organic fertilizer and liquid organic fertilizer. Subplot consisted of three levels and 1 , 3, and 5 seedlings per hole. The data were analyzed using analysis of variance with Costat program. Results of statistical analysis showed that one interaction between the use of the number of seedling and organic fertilizers no real effect on the variables tested. The number of seedling treatment use did not significantly affect to the growth and yield, except the total number of tillers. Treatment of solid organic fertilizer is better than liquid organic fertilizer on the growth and yield of rice. Dry grain yield per harvested and oven dried clumps on the use of solid organic fertilizer is higher, at 22,69 g and 14,85 g, compared to using liquid organic fertilizer 15,11 g and 8,19 g. Associated with the use of the number of seeds is recommended to use the number of seeds one per hole, but for the implementation in the field required further research.